The Influence of Organizational Culture and Personality on the Performance of Wahana Kalpika Jakarta Cooperative Microtrans Drivers with Job Satisfaction as an Intervening Variable - Roy Rozinaldo Pattikawa; Nancy Yusnita; Yayan Hadiyat (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This study aims to analyze the influence of organizational culture and personality on the performance of Mikrotrans drivers, with job satisfaction as an intervening variable, at the Wahana Kalpika Cooperative in Jakarta. The approach used is quantitative with a survey method. The sampling technique used simple random sampling, with a research sample of 330 Mikrotrans KWK drivers in East Jakarta, considered representative of the population. Data was collected thru questionnaires and analyzed using SmartPLS software version 4 with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The research results indicate that organizational culture and personality have a positive and significant impact on driver performance. Job satisfaction has a positive but non-significant effect on performance. Additionally, organizational culture has a positive and significant effect on job satisfaction, while personality has a positive but non-significant effect on job satisfaction. Indirectly, organizational culture significantly affects performance thru job satisfaction, while personality does not show a significant mediating effect thru job satisfaction.